Effects of β-glucan polysaccharide revealed by the dominant lethal assay and micronucleus assays, and reproductive performance of male mice exposed to cyclophosphamide - Oliveira, Rodrigo Juliano; Pesarini, João Renato; Salles, Maria José Sparça; Kanno, Tatiane Yumi Nakamura; Lourenço, Ana Carolina Dos Santos; Leite, Véssia Da Silva; Silva, Ariane Fernanda Da; Matiazi, Hevenilton José; Ribeiro, Lúcia Regina [UNESP]; Mantovani, Mário Sérgio (Sociedade Brasileira de Genética, 2014)
β-glucan is a well-known polysaccharide for its chemopreventive effect. This study aimed to evaluate the chemopreventive ability of β-glucan in somatic and germ cells through the dominant lethal and micronucleus assays, and its influence on the reproductive performance of male mice exposed to cyclophosphamide. The results indicate that β-glucan is capable of preventing changes in DNA in both germ cells and somatic ones. Changes in germ cells were evaluated by the dominant lethal assay and showed damage reduction percentages of 46.46% and 43.79% for the doses of 100 and 150 mg/kg. For the somatic changes, evaluated by micronucleus assay in peripheral blood cells in the first week of treatment, damage reduction percentages from 80.63-116.32% were found. In the fifth and sixth weeks, the percentage ranged from 10.20-52.54% and -0.95-62.35%, respectively. Besides the chemopreventive efficiency it appears that the β-glucan, when combined with cyclophosphamide, is able to improve the reproductive performance of males verified by the significant reduction in rates of post-implantation losses and reabsorption in the mating of nulliparous females with males treated with cyclophosphamide.
Keywords: mutation; post-implantation losses; chemoprevention; micronucleus; nulliparous females